Pengaruh Model Pembelajaran VCT (Value Clarificasion Technique) Terhadap Hasil Belajar PKN SISWA Kelas IV SD Inpres Lewintana Tahun Ajaran 2020 - Asya Rumantanra; Nisa, Khairun; Istiningsih, Siti (Pendagogia: Jurnal Pendidikan Dasar, 2022)
This study aims to determine the effect of the VCT (Value Clarification Technique) learning model on PPKn learning outcomes for fourth grade students of SD Inpres Lewintana. This type of research is a quantitative research type of experiment with a Quasi-Experimental type of Nonequivalent control group design. The population in this study were all fifth grade students of SD Inpres Lewintana, while the samples were grade IVb students of SD Inpres Lewintana as the experimental class and grade IVa students of SD Inpres Lewintana as the control class. The results of the normality and homogeneity tests carried out obtained data stating that the data were normally distributed and had homogeneous variants so that hypothesis testing could be carried out. The results of the t test obtained the value of sig. 2 tailed of 0.019, which is less than 0.05, which means Ha is accepted, indicating that there is an influence of the VCT (Value Clarification Technique) learning model on the learning outcomes of fourth grade PPKn students at SD Inpres Lewintana for the 2021/2022 academic year.